Presencia de interleuquina 8 en fluido crevicular de pacientes con periodontitis agresiva (2005)
ABSTRACT: The aggressive periodontitis is associated to the presence of periodontal pathogens and altered response in the polymorph nuclear Neutrophils (PMN). The interleukin 8(IL-8) recruits and activates these cells in infection sites. This paper analyzes the presence of IL-8 in crevicular fluid, of 17 patients with aggressive periodontitis and 11 healthy or with minor gingivitis individuals (controls). In all of them, it was carried out medical evaluation, attachment level (AL), plaque index(PI), bleeding on probing index(BP) and crevicular fluid volume (CFV) using Periotron 8000. Concentration and total amount of Interleukin 8 in CFV are measured by ELISA. Statistical analyses are carried out with the programs Prism 4.0 and Log Xact 4.1. There are not significant differences between patients and controls with regard to their age and oral hygiene. Patients and controls with mean age of 36.94 (SD 8.62) and of 30.18 (SD 8.61) present IP = 49.35% (SD 24.65) and 34.27% (SD 19.45) respectively. The patients differed from the controls in their AL (p = 0.000039), BP (p = 0.007) and CFV (p = 0.00001) values. The concentration of IL-8 in patients (315.4 pg/ ìL) and controls (426.4 pg/ ìL) does not show differences (p > 0.05), but the total amount of IL-8 is different (median 1844.06 and 229.87 pg, p=0.0013, respectively). In summary there is association among Aggressive Periodontitis, AL, VFC and the total content of IL-8. This study shows the importance of IL-8 in the response of Neutrophils.